Ambient air pollution and the prevalence of obesity in chinese children: The seven northeastern cities study. (11th February 2014) - Dong, Guang‐Hui; Qian, Zhengmin (Min); Liu, Miao‐Miao; Wang, Da; Ren, Wan‐Hui; Flick, Louise H.; Fu, John; Wang, Jing; Chen, Weiqing; Simckes, Maayan; Trevathan, Edwin
<x xml:space="preserve">Abstract</x> Objective The association between air pollution and the prevalence of overweight and obesity is evaluated. Methods The population consisted of 30, 056 children (aged 2‐14 years), randomly selected from 25 districts in Northeast China. Child weight and height were measured, and exposures to particulate matter with an aerodynamic diameter ≤10 μm (PM10), sulfur dioxide (SO2), nitrogen dioxides (NO2), and Ozone (O3) were estimated from the data collected at monitoring stations in the 25 districts. Using two‐level logistic models, we examined the association between the exposure and the prevalence of overweight and obesity. Results Among the study children, 12.3% (3, 704) were overweight and 14.1% (4, 233) were obese. After adjusting for confounding factors, an increased prevalence of obesity was associated with an interquartile range increase in PM10 (31 μg/m3 ; odds ratio [ORs] = 1.19; 95% confidence interval [CI]: 1.11‐1.26), SO2 (7.4 ppb; ORs = 1.11; 95% CI: 1.03‐1.20), NO2 (5.3 ppb; ORs = 1.13; 95% CI: 1.04‐1.22), and O3 (11.5 ppb; ORs = 1.14; 95% CI: 1.04‐1.24). Prevalence of overweight increased with an interquartile range increase in O3 (11.5 ppb; ORs = 1.09; 95% CI: 1.03‐1.15). Conclusions This study suggests that air pollution is positively associated with an increased likelihood of obesity or overweight in children.